Natural biomass-derived carbon dots as a potent solubilizer with high biocompatibility and enhanced antioxidant activity - Wu, Tong; Li, Menghan; Li, Tingjie; Zhao, Yafang; Yuan, Jinye; Zhao, Yusheng; Tian, Xingrong; Kong, Ruolan; Zhao, Yan; Kong, Hui; Zhang, Yue; Qu, Huihua (Frontiers in Molecular Biosciences, 2023)
Numerous star natural compounds exhibit low bioavailability owing to suboptimal water solubility. The modern pharmaceutical industry currently employed in contemporary pharmaceutical research are characterized by low efficiency, sophisticated technological requirements and latent adverse effects. A pressing exigency exists for the elucidation and implementation of a novel solubilizer to ameliorate these challenges. Our antecedent study identified natural biomass-derived carbon dots as a promising candidate. In the present study, we report on natural fluorescent carbon dots sourced from Aurantia Fructus Immatures (AFI-CDs), which have exhibited a remarkable solubilization effect, augmenting naringin solubility by a factor of 216.72. Subsequent analyses suggest that the solubilization mechanism is potentially contingent upon the oration of a nanostructured complex (NA-AFI-CDs) between AFI-CDs and NA, mediated by intermolecular non-covalent bonds. Concomitantly, the synthesized NA-AFI-CDs demonstrated high biocompatibility, exceptional stability, and dispersion. In addition, NA-AFI-CDs manifested superior free radical scavenging capacity. This research contributes foundational insights into the solubilization mechanism of naringin utilizing AFI-CDs and proffers a novel strategy circumventing the challenges associated with low aqueous solubility of waterinsoluble drugs in the field of modern pharmaceutical science.